2017
DOI: 10.1016/j.heliyon.2017.e00294
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency cogeneration boiler bagasse-ash geochemistry and mineralogical change effects on the potential reuse in synthetic zeolites, geopolymers, cements, mortars, and concretes

Abstract: Sugarcane bagasse ash re-utilisation has been advocated as a silica-rich feed for zeolites, pozzolans in cements and concretes, and geopolymers. However, many papers report variable success with the incorporation of such materials in these products as the ash can be inconsistent in nature. Therefore, understanding what variables affect the ash quality in real mills and understanding the processes to characterise ashes is critical in predicting successful ash waste utilisation. This paper investigated sugarcane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…The original BA was unsuitable for applications as low-reactivity pozzolanic materials in concretes because of their high porosity and large particle sizes. Chao and Kuo [ 2 ] and Clark et al [ 3 ] revealed that the filler effects and pozzolanic activities of industrial ashes depend on their fineness and particle size. Therefore, using a Los Angeles grinding machine (ELE International, Bedfordshire United Kingdom) for 3.0 h at a rotating speed of 33.0 rpm, the original BA was dried to reduce their moisture contents to about 1.0–2.0% (dry basis) and was ground until the particles were less than 15% by mass and retained on a 45 micrometer (µm) sieve.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The original BA was unsuitable for applications as low-reactivity pozzolanic materials in concretes because of their high porosity and large particle sizes. Chao and Kuo [ 2 ] and Clark et al [ 3 ] revealed that the filler effects and pozzolanic activities of industrial ashes depend on their fineness and particle size. Therefore, using a Los Angeles grinding machine (ELE International, Bedfordshire United Kingdom) for 3.0 h at a rotating speed of 33.0 rpm, the original BA was dried to reduce their moisture contents to about 1.0–2.0% (dry basis) and was ground until the particles were less than 15% by mass and retained on a 45 micrometer (µm) sieve.…”
Section: Methodsmentioning
confidence: 99%
“…The gSCC specimens were utilized to establish the optimal percentages of GCW associated with BA and RHA [ 3 ]. At a constant of 1:2.15, a binder to aggregate mortars was set by mass as outlined by ASTM C39 [ 24 ].…”
Section: Optimal Content Of Gcwmentioning
confidence: 99%
See 2 more Smart Citations
“…Durante o processo de combustão do bagaço, a temperatura das caldeiras (300ºC a 1.000ºC) pode produzir cinzas com diferentes tonalidades de cor [49], bem como determinará o aparecimento das diferentes fases estruturais (amorfa ou cristalina) de sílica [13,47]. Além da temperatura, o tempo de queima também pode afetar a forma estrutural, a quantidade e as características físicas da sílica [48,50].…”
Section: Introductionunclassified